Integration of Pancasila and Islamic values in Indonesia's futuristic education transformation: Multicultural analysis - Widiastuti, Anik; MR, Moh Irsyad Fahmi; Widodo, Syukri Fathudin Achmad; Ahmed, Touheed; Shahzeb, Shahzeb (Journal of Social Studies (JSS), 2024)
This research aims to analyze the integration of Pancasila and Islamic values in the context of futuristic educational transformation in Indonesia with a multicultural approach. Facing the era of industrial revolution 4.0 and society 5.0, Indonesian education needs to transform without losing the roots of the nation's noble values. The research method used is descriptive qualitative with a literature study approach. The research results show that there is harmony between the values of Pancasila and Islamic teachings which can be integrated into futuristic education. Soft skills development based on these two value systems is very important in preparing future generations. The integration model can be implemented through the development of an integrated curriculum and innovative learning methods such as project-and role-based learning, and the formation of cross-cultural communities. This multicultural approach in the integration process strengthens understanding of diversity while maintaining unity. Although there are challenges in implementation, strategies such as intensive teacher training and multi-stakeholder collaboration can be a solution. This research contributes to the development of an educational model that integrates national and religious values to face the challenges of the digital era in Indonesia.